THE SUBSTANTIVE CRIMINAL PROTECTION OF THE JUVENILE DELINQUENT - Abidi, Nihad Ali Malik Abidi; Rami Abdel Hay (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2025)
Objective: This study examines juvenile delinquency as a complex social issue that poses significant risks to both individuals and society, focusing on the substantive criminal protection mechanisms established in Iraq and Lebanon. Method: The research adopts an analytical and comparative legal approach, reviewing legislative texts, judicial rulings, and doctrinal perspectives to assess the strengths and weaknesses of the two juvenile justice systems. Results: The findings reveal that while both countries have made progress in developing juvenile justice frameworks, substantial gaps remain, particularly in addressing recidivism, ensuring adequate rehabilitation, and incorporating preventive social protection mechanisms. These shortcomings limit the effectiveness of existing legislative measures and hinder the reintegration of juvenile offenders. Novelty: The study contributes by providing a cross-national comparative analysis that not only identifies legislative deficiencies but also proposes reform-oriented solutions aligned with international standards. This highlights the need for comprehensive policies that balance legal accountability, protection, and rehabilitation to strengthen juvenile justice systems in the region.